Risk factors of distal segment aortic enlargement after complicated type B aortic dissection - Yu Shen; Simeng Zhang; Guanglang Zhu; Yanqing Chen; Zheng Chen; Zaiping Jing; Qingsheng Lu (Journal of Interventional Medicine, 2019)
Objectives: Distal segment aortic enlargement (DSAE) is a common complication that influences the long-term prognosis of type B aortic dissection (TBAD) after thoracic endovascular aortic repair (TEVAR). In this study, a multivariate analysis was performed to find potential factors predictive of DSAE. Methods: A single-center retrospective study was performed from 1999 to 2016. Included in the study were complicated TBAD patients who underwent TEVAR with uncovered residual tears. Based on the diameter of the distal segment of the uncovered aorta, we assigned patients to an enlargement group and a non-enlargement group. Data extracted from the medical records included demographic and clinical characteristics and follow-up computed tomography angiography data. The primary endpoints were the all-cause mortality and the presumably aortic-related events that required reintervention during the follow-up period. Results: For the 333 patients, all-cause mortality was 38 (11.41%), and 76 (22.82%) patients underwent reintervention. A total of 70 (21.02%) patients experienced DSAE, among them were 2 patients who died of aortic rupture and 58 patients who accepted reintervention. Multivariate analysis reviewed independent risk factors of postoperative DSAE, including current smoking, the residual length of the patent false lumen, the postoperative number of dissection tears in the thoracic aorta and type III aortic arch; as well as protective factors, including the application of a restrictive bare stent (RBS), the length of covered stent in the descending thoracic aorta, and the distance from the residual first tear to the left subclavian artery (LSA). Conclusion: DSAE after TEVAR for patients with a complicated TBAD can be influenced by their current smoking habit, the residual length of patent false lumen, the postoperative number of dissection tears in the thoracic aorta and the aortic arch type. Meanwhile, RBS usage, the length of the covered stent in the descending thoracic aorta and the distance from the residual first tear to the LSA could have positive effect on the prognosis. Keywords: Type B aortic dissection, Thoracic endovascular aortic repair, Distal segment aortic enlargement, Risk factor